2016
DOI: 10.1097/coc.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Therapy in Advanced Cutaneous Squamous Cell Carcinoma (CSCC)

Abstract: Platinum-based therapy remains as one of the standard options in advanced CSCC management. Agents to improve response rates are needed and future trials should address the use of novel targeted and new chemotherapy combinations in CSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Investigation of systemic therapies for advanced cSCC has been limited to a few prospective trials, and most of the time, retrospective data concern a highly selected population. Cisplatin-based combination chemotherapies are the most commonly used treatment, with an overall response rate of up to 80% [8][9][10]. Nevertheless, most of the time, this efficacy is not durable.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of systemic therapies for advanced cSCC has been limited to a few prospective trials, and most of the time, retrospective data concern a highly selected population. Cisplatin-based combination chemotherapies are the most commonly used treatment, with an overall response rate of up to 80% [8][9][10]. Nevertheless, most of the time, this efficacy is not durable.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,5 Preclinical studies and clinical case reports have shown that the high mutation burden 20 coupled with observed immunosuppression in instances of cutaneous SCC progression implicates a utility for targeting immune checkpoint elements such as those in the PD-1 pathway. 3,5 …”
Section: Discussionmentioning
confidence: 99%
“…Serial testing of thyroid, liver and renal function was performed on follow-up to monitor for reported adverse outcomes. 3 The patient was followed for clinical outcome on an observational study. 9 …”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…These strategies lack durability, and overall survival for mcSCC is only 10.9 months. 2 Clinical responses in mcSCC have recently been reported with the use of PD-1 antibodies, pembrolizumab and nivolumab. 3 , 4 , 5 Here we report a complete pathologic response after 4 cycles of nivolumab and the anti–CTLA-4 antibody, ipilimumab, in a patient with mcSCC.…”
Section: Introductionmentioning
confidence: 99%